2002
DOI: 10.1103/physrevb.66.060402
|View full text |Cite
|
Sign up to set email alerts
|

Spin reduction transition in spin-32random Heisenberg chains

Abstract: Random spin-3 2 antiferromagnetic Heisenberg chains are investigated using an asymptotically exact renormalization group. Randomness is found to induce a quantum phase transition between two random-singlet phases. In the strong randomness phase the effective spins at low energies are S e f f ϭ 3 2 , while in the weak randomness phase the effective spins are S e f f ϭ 1 2 . Separating them is a quantum critical point near which there is a nontrivial mixture of spin-1 2 , spin-1, and spin-3 2 effective spins at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 23 publications
(76 reference statements)
6
56
1
Order By: Relevance
“…21, which has a random-singlet ground state. A similar situation prevails in the case of the spin-3/2 Heisenberg model: 28 the decimation rules for the spin model are almost exactly the same as the fusion rules for SU͑2͒ 3 ͑except for the Heisenberg model not allowing the fusion 1 1=1, which could be corrected by allowing biquadratic coupling͒.…”
Section: B S ͼ 1 õ 2 Heisenberg Chains and The Su(2) K Fusion Algebramentioning
confidence: 98%
“…21, which has a random-singlet ground state. A similar situation prevails in the case of the spin-3/2 Heisenberg model: 28 the decimation rules for the spin model are almost exactly the same as the fusion rules for SU͑2͒ 3 ͑except for the Heisenberg model not allowing the fusion 1 1=1, which could be corrected by allowing biquadratic coupling͒.…”
Section: B S ͼ 1 õ 2 Heisenberg Chains and The Su(2) K Fusion Algebramentioning
confidence: 98%
“…These fixed points were dubbed the S n permutation symmetric points, with n =2S + 1 the number of competing domains. [7][8][9][10] Because of the unique structure of their Hilbert spaces, disordered anyonic chains are particularly amenable to treatment via strong randomness renormalization-group ͑RG͒ methods and indeed have been shown to exhibit infiniterandomness fixed points. 11,12 They are thus an especially fertile ground for trying to discover and classify new universality classes of strongly random behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we have concluded that the mean-field type calculation, in spite of its simplicity and limitations such as the correlation of spin fluctuations have not been considered, is still an adequate starting point, in which within this theoretical framework it is easy to determine the complete phase diagrams. It also predicts the existence of multicritical points in simple, such as spin-1 2 Ising model [18] …”
Section: Summary and Discussionmentioning
confidence: 99%
“…Finally, we should also mention that recently many researches have investigated the antiferromagnetic spin- Moreover, random spin-3 2 antiferromagnetic Heisenberg chains [18] and the random quantum antiferromagnetic spin-3 2 chain [19] have been studied using the RG calculations.…”
Section: Introductionmentioning
confidence: 99%